Protected areas do not mitigate biodiversity declines: A case study on butterflies. Issue 2 (16th November 2018) - Rada, Stanislav; Schweiger, Oliver; Harpke, Alexander; Kühn, Elisabeth; Kuras, Tomáš; Settele, Josef; Musche, Martin
Abstract: Aim: To assess the effectiveness of protected areas in preventing biodiversity decline. We first test whether species richness of butterfly assemblages is higher within European Natura 2000 (N2000) sites than in their surroundings. We then assess temporal trends in butterfly richness and test whether these trends differ inside and outside the N2000 network. Location: Germany, Europe. Methods: We utilized generalized linear mixed‐effects models (GLMM) to analyse an 11‐year data series on species richness of butterfly assemblages collected on 245 transects across Germany, located inside and outside N2000 sites, and comprising a total of 122 butterfly species. Results: Butterfly species richness was highest inside N2000 protected areas, while outside it constantly declined with increasing distance from N2000 sites. We found an overall decline in species richness by 10% within 11 years. This decline neither differed between transects located inside or outside the N2000 network nor varied with distance from N2000 sites. Main conclusions: The higher species richness inside the N2000 network underlines their proper designation and their potential for the conservation of biodiversity. However, the current negative trend in butterfly species richness across Germany is not mitigated by the N2000 network, and we assume insufficient management or measures targeted at other organisms than butterflies as potential reasons.